Elucidating the kinetics and mechanisms of tetramethrin biodegradation by the fungal strain Neocosmospora sp. AF3 - Wen-Juan Chen; Xiaofang Luo; Xuanrui Zhang; Kalpana Bhatt; Shao-Fang Chen; Mohamed A. Ghorab; Xiaofan Zhou; Yaohua Huang (Microbial Cell Factories)
Abstract Tetramethrin is a common pyrethroid insecticide, but there is limited knowledge about its degradation kinetics and mechanisms. In this study, a novel fungal strain, Neocosmospora sp. AF3, was obtained from pesticide-contaminated fields and was shown to be highly effective for degrading tetramethrin and other widely used pyrethroids. The AF3 strain completely removed 10 mg/L of tetramethrin from mineral salt medium in 9 days. The first-order kinetic analysis indicated that the degradation rate constant of the AF3 strain on 50 mg/L tetramethrin was 0.2835 d−1 (per day), and the half-life was 2.45 days. A response surface model analysis showed that the optimal degradation conditions for the AF3 strain are a temperature of 33.37 ℃, pH of 7.97, and inoculation amount of 0.22 g/L dry weight. The Andrews nonlinear fitting results suggested that the optimal concentration of tetramethrin metabolized by the AF3 strain is 12.6073 mg/L, and the q max, K i, and K s values were 0.9919 d−1, 20.1873 mg/L, and 7.8735 mg/L, respectively. The gas chromatography–mass spectrometry (GC–MS) analysis indicated that N-hydroxymethyl-3,4,5,6-tetrahydrophthalimide, chrysanthemic acid and tetrahydrophthalimide are the main intermediates involved in the metabolism of tetramethrin by the AF3 strain. Furthermore, this strain was shown to effectively degrade other pyrethroid pesticides including permethrin, beta-cypermethrin, chlorempenthrin, fenvalerate, d-cyphenothrin, bifenthrin, meperfluthrin, cyfluthrin, and deltamethrin within a short period, suggesting that Neocosmospora sp. AF3 can play an important role in the remediation of pyrethroid contamination. Taken together, these results shed a new light on uncovering the degradation mechanisms of tetramethrin and present useful agents for developing relevant pyrethroid bioremediation strategies.